EDITORIAL: 30 YEARS - Hayes, Grahame (PINS-Psychology in Society, 2025)
PINS (Psychology in society) appeared 30 years ago now, its first issue being dated September 1983. At one level this is quite unremarkable, and yet in the world of independent journals, both locally and internationally, it is something to acknowledge, maybe even celebrate. Many very fine journals, again both locally and internationally, have sadly ceased production, or only appear annually, or only in electronic form. As a way of ensuring continued and regular production a number of independent journals have entered into partnerships with publishing houses. Obviously one of the main advantages of being independent is the complete control over editorial and publishing policy, and being responsible to one’s intellectual peers on the editorial board. The main disadvantage is the relative lack of resources to produce the journal. Most independent journals rely on the “free labour” of editors to produce the journal, and given that the editors have busy jobs the time taken to work on the journal is often “stolen” from other work-related activities.